2014
DOI: 10.1021/bm401583b
|View full text |Cite
|
Sign up to set email alerts
|

Clearance Kinetics of Biomaterials Affects Stem Cell Retention and Therapeutic Efficacy

Abstract: The use of biomaterial carriers to improve the therapeutic efficacy of stem cells is known to augment cell delivery, retention, and viability. However, the way that carrier clearance kinetics boosts stem cell delivery and impacts stem cell function remains poorly characterized. In this study, we designed a platform to simultaneously quantify carrier clearance and stem cell retention to evaluate the impact of carrier clearance kinetics on stem cell retention. Additionally, a murine model of hindlimb ischemia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Therefore, in this study, HA hydrogel combined with CB‐MNC was used for the same approach after acute MI to investigate whether cell retention rate was improved. HA is a type of extracellular matrix with a rapid degradation rate (half‐life: 15–25 hours) [46]. Although HA degraded rapidly, we still found that the cell retention rate was increased approximately twofold in the CB‐MNC and HA combined group.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, in this study, HA hydrogel combined with CB‐MNC was used for the same approach after acute MI to investigate whether cell retention rate was improved. HA is a type of extracellular matrix with a rapid degradation rate (half‐life: 15–25 hours) [46]. Although HA degraded rapidly, we still found that the cell retention rate was increased approximately twofold in the CB‐MNC and HA combined group.…”
Section: Discussionmentioning
confidence: 72%
“…Although HA degraded rapidly, we still found that the cell retention rate was increased approximately twofold in the CB-MNC and HA combined group. Despite the short half-life of HA in vivo, it has been shown to benefit the injured heart by reducing scar formation and increasing cell survival and retention, neovascularization, and the efficacy of cell therapy in both rat and swine MI models [27,46,47]. In this study, we found that cell retention rate was increased approximately twofold in the CB-MNC and HA combined group.…”
mentioning
confidence: 57%
“…It would be important to be able to monitor changes in scaffold composition non-invasively over time, as stem cells are particularly sensitive to changes in environmental cues, including the physical microenvironment and mechanical stress [710]. Indeed, a recent imaging study using Alexa Fluor-labeled HA reported that the clearance kinetics of biomaterials affects stem cell retention and therapeutic efficacy [11]. However, optical imaging is limited to small animal studies and does not directly report on the molecular structure of the hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these problems, cell therapy has been introduced using biocompatible and biodegradable biomaterials to reduce cell loss and long-term in vitro retention of stem cells. Currently in clinical trials, these biomaterials are widely used in drug and cell-delivery systems, regenerative medicine and tissue engineering in which to prevent the long-term survival of foreign substances in the body the release of cells are controlled (40).…”
Section: Application Of Mscs In Regenerative Medicine In Animal Modelsmentioning
confidence: 99%